Transcranial direct current stimulation for treatment-resistant obsessive-compulsive disorder: report on two cases and proposal for a randomized, sham-controlled trial - Silva, Renata de Melo Felipe da (2016)
CONTEXT AND OBJECTIVE: Neuromodulation techniques for treating obsessive-compulsive disorder (OCD) have expanded through greater understanding of the brain circuits involved in this disorder. Transcranial direct current stimulation (tDCS), a non-invasive technique, has been studied as an alternative for treatment-resistant OCD. We describe the design of a clinical trial using tDCS for OCD and report on the outcomes from two patients with primary OCD who were resistant to cognitive-behavioral therapy and to selective serotonin reuptake inhibitors, and who received tDCS in an open manner during the training phase for the study procedures. DESIGN AND SETTING: Methodological description of a clinical trial using tDCS for treatment-resistant OCD at a university hospital; and a report on two cases. METHODS: The proposed study is randomized, sham-controlled and double-blind. Forty-four patients will be randomized to either active or sham intervention. The active intervention consists of applying an electric current of 2 mA, with the cathode positioned in the region corresponding to the supplementary motor cortex (bilaterally) and the anode positioned in the deltoid. The primary outcome will be the reduction in baseline YBOCS (Yale-Brown Obsessive Compulsive Scale) score at the end of week 4. The secondary outcomes will be depression and anxiety symptoms. Genetic markers, cortical excitability and neurocognitive performance will be investigated. RESULTS: The first patient showed significant improvement, whereas the second remained symptomatic after four weeks and after six months. tDCS was well tolerated. CONCLUSION: tDCS for treatment-resistant OCD merits randomized controlled trials that test its effectiveness. CLINICAL TRIAL REGISTRATION: NCT02743715